Balancing the risk of spontaneous ischemic and major bleeding events in acute coronary syndromes - Ducrocq, Grégory; Katus, Hugo (American heart journal, 2017)
Background Evaluation of antithrombotic treatments for acute coronary syndromes (ACS) requires balancing ischemic and bleeding risks to assess net benefit. We sought to compare the relative effects of ischemic and bleeding events on mortality. Methods: In the PLATelet inhibition and patient Outcomes (PLATO) trial, we compared spontaneous ischemic events (myocardial infarction or stroke) with spontaneous major bleeding events (PLATO major, Thrombolysis In Myocardial Infarction [TIMI] major, Global Utilization of Streptokinase and Tissue Plasminogen Activator for Occluded Coronary Arteries [GUSTO] severe) with respect to risk of mortality using time-dependent Cox proportional hazards models. The comparison was performed using ratio of hazard ratios for mortality increase after ischemic vs bleeding events. Results: A total of 822 patients (4.4%) had ≥1 spontaneous ischemic event; 485 patients (2.6%), ≥1 spontaneous PLATO major bleed, 282 (1.5%), ≥1 spontaneous TIMI major bleed; and 207 (1.1%), ≥1 spontaneous severe GUSTO bleed. In patients who had both events, bleeding occurred first in most patients. Regardless of classification, major bleeding events were associated with increased short- and long-term mortality that were not significantly different from the increase associated with spontaneous ischemic events: ratio of hazard ratios (95% CIs) for short- and long-term mortality after spontaneous ischemic vs bleeding events: 1.46 (0.98-2.19) and 0.92 (0.52-1.62) (PLATO major); 1.26 (0.80-1.96) and 1.19 (0.58-2.24) (TIMI major), 0.72 (0.47-1.10) and 0.83 (0.38-1.79) (GUSTO severe) (all P > 0.05). Conclusions: In patients with ACS on dual antiplatelet therapy, spontaneous major bleeding events seem “prognostically equivalent” to spontaneous ischemic complications. This result allows quantitative comparisons between both actual and predicted bleeding and ischemic risks. Our findings help to better define net clinical benefit of antithrombotic treatments and more accurately estimate mortality after ischemic and bleeding events in patients with ACS. (Am Heart J 2017;186:91-9.)